2011
DOI: 10.1097/mjt.0b013e3181d070c3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tolerability of Lithium With a Once-Daily Dosing Schedule

Abstract: Lithium has been proved to be highly efficacious in the treatment of bipolar affective disorder, though a narrow therapeutic index and a high incidence of troublesome side effects often leads to poor compliance in patients. Therefore, there is a need to explore treatment strategies to improve the efficacy and side effect profile of lithium. We compared the efficacy and side effect profile of a once-daily versus twice-daily dosing schedule of lithium in mania. Eighty-three manic patients according to Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
0
17
1
2
Order By: Relevance
“…Perhaps most importantly, only a single trial examined patients newly starting on lithium. 29 It is established that lithium causes renal impairment, such as reduced urinary concentrating ability, yet it is not known when, if ever, this becomes irreversible; therefore, studying SDD in patients previously exposed to MDD may fail to show any difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps most importantly, only a single trial examined patients newly starting on lithium. 29 It is established that lithium causes renal impairment, such as reduced urinary concentrating ability, yet it is not known when, if ever, this becomes irreversible; therefore, studying SDD in patients previously exposed to MDD may fail to show any difference.…”
Section: Discussionmentioning
confidence: 99%
“…29 Among the 2 trials that compared renal biopsy results, both found significantly more pathologic damage to the kidneys in patients receiving lithium in MDD. 18,37 In addition to examining renal effects, it is important when proposing a dosage regimen change to also examine other adverse effects and clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term studies reported approximately a 15% incidence of irreversible decrease in the urinary concentrating ability of lithium users 51,52 . This effect can be more frequently found with lithium administered twice daily as compared with a single administration of an extended release formulation 53,54 . A study using other markers of kidney damage, such as β2-microglobulin (associated with proximal tubular injury) and glucosaminoglycan (component of the glomerular basement membrane) in 107 lithium users between 1 and 15 years with bipolar disorder were compared with 29 controls with other psychiatric disorders 55 .…”
Section: Renal Impairmentmentioning
confidence: 98%